Lipid disorders in children living with overweight and obesity- large cohort study from Poland - Brzeziński, Michał (Lipids Health Dis, 2020)
BACKGROUND: While in the general paediatric population the presence of abnormal lipid values is estimated at 8–20%, depending on the population, accepted norms and age, it was shown that in the population of lean children the prevalence of dyslipidemia is lower than in obese children, in whom it ranges from 20 to over 40%. Until now, however, no results of similar studies on a large sample of children form a Central or Eastern European country have been published. The aim of this study was to evaluate the prevalence of lipid disorders in overweight and obese children and adolescents participating in an integrated weight reduction programme. METHODS: According to the “6-10-14 for Health” programme implementation schedule, the programme accepted patients living in Gdańsk, aged 6, 9–11 and 14 years old, with BMI above the 85th percentile for age and sex, according to the Polish percentile charts. During the first visit, each of the participants underwent basic anthropometric examinations - body weight, body height, waist and hip circumference, blood pressure and body composition by bioelectrical impedance were measured. Blood samples were taken to assess lipid, glucose and insulin levels as well as alanine transaminase (ALT) and thyroid stimulating hormone (TSH) activity. RESULTS: 1948 patients underwent full anthropomethric and blood work measurements. At least one of the lipid disorders occurred in 38.23% of girls and 40.51% of boys with overweight and obesity. The most common lipid disorderswere decreased high-density lipoprotein cholesterol (HDL-C) levels (present in 20.55% of the girls and 23.79% of the boys) and elevated low-density lipoprotein cholesterol (LDL-C) (present in 15.31% of the girls and 14.25% of the boys). There was no strong association between lipid disorders and age, sex, birth weight, gestational age at birth or body composition. CONCLUSIONS: Such a frequent occurrence of lipid disorders in the population of children and adolescents should be an important warning signal both at the individual and population level. Not only effective screening methods for overweight and obese children should be implemented from an early age but also therapeutic measures are required. TRIAL REGISTRATION: The trial is registered under the Local Ethics Committee at Medical University of Gdańsk, decision No. NKBBN/228/2012 from 25 June 2012.